IMPLEMENTACE PRVKŮ PRO SKATEBOARDING DO VEŘEJNÉHO PROSTORU - Kotal, Jiří; Kotal Jiří (České vysoké učení technické v Praze, 2018)
Tématem diplomové práce je vztah veřejného prostoru a skateboardingu. Popisuje skateboarding jako nedílnou součást společnosti a snaží se o jeho jasné začlenění do veřejného prostoru. Vyhodnocuje skateboarding jako pozitivní městotvornou aktivitu, která zkvalitňuje prostor, vytváří kulturu a zlepšuje diverzitu města. Cílem práce je prověřit vytipovaná místa v centru Prahy implementací prvků pro skateboarding a uchopit tuto aktivitu jako jeden z parametrů pro návrh veřejného prostoru.

The main topic of my thesis is the relationship between public space and skateboarding. It describes skateboarding as an integral part of society and seeks ways to include it into contemporary public space. It evaluates skateboarding as a positive activity, co-shaping our cities, that, at the same time, cultivates public space, creates another layer of culture and thus diversifies not cities. The aim of this work is to examine various selected sites in Prague's broader centre by implementing elements for skateboarding and establish this activity as a permanent parameter in the process of designing public spaces.
IMPLEMENTATION OF THE ELEMENTS FOR SKATEBOARDING INTO PUBLIC SPACE
Keywords: Skateboarding,Veřejný prostor,doprava,volnočasové aktivity,Subkultura; Skateboarding,Public space,Transport,leisure activities,Subculture